Pengaruh Jarak Antar Fondasi Dan Kekasaran Terhadap Daya Dukung Fondasi Tiang Kelompok - Sayoga, Davin; Fatnanta, Ferry; Nugroho, Soewignjo Agus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Upper soil crust of coastal area in Indonesia consists of greatly-thick soft soil. Therefore, the use of end-bearing type pile foundation on that kind of area is highly discouraged due to how expensive it is economically. Friction pile becomes an alternative foundation for coastal area, however there is still little friction between pile surface and soil due to concrete and steel’s smooth surface. Pile modification via improving pile surface’s coarseness can be considered as an alternative for improving friction force between pile and soil. This study aims to determine the effect of pile surface coarseness towards pile surface’s bearing capacity. This study was conducted by making a varying type of coarseness of the pile surface and distance between piles. The first type of coarseness is matched with pile with concrete ingredient. The second type of coarseness is made with stone shards which cover the pile surface in its entirety. The third type of coarseness is a variance of how the first and second coarseness are made, however with same length between segments. The observation was conducted in a laboratory and with loading test applied on the pile model. The test results were analyzed with graphic method. The resulting study shows that there is an improvement in bearing capacity. Foundation with coarseness on its surface has higher Qult value (98,03% - 134,63%) than those without coarseness. Keywords : Soft Soil, Pile Foundation, Coarseness, Static Loading Test, Interpretation of Loading Test